Market signals from online behavior - Olynk Widmar, Nicole J.; Smith, Michael L.; Robinson, Erin (Consumer Corner, 2025)
What do social media trends, Google searches, and online chatter reveal about consumer behavior? And, How can we interpret these signals without losing sight of the people behind the posts? This book examines the digital traces left by consumers and explores how these signals intersect with food, agriculture, retail, and beyond. Drawing from real-time data and social-listening analysis, Market Signals connects the dots between what is trending online and what it means for markets in the real world. Whether it is the rise of plant-based eating, changing holiday shopping norms, or shifting attitudes toward convenience and cost, the consumer voice online often reflects more than opinion. It signals action. Blending applied research with cultural commentary, Nicole J. Olynk Widmar and her team highlight what it means to listen to contemporary consumers, and how those insights shape, reflect, and sometimes surprise the industries built to serve them. For agribusiness professionals, communicators, and anyone trying to keep pace with an ever-evolving consumer landscape, Market Signals From Online Behavior offers a grounded yet agile perspective on the many ways we can learn from customers, even when they are not speaking to us directly. -- From back of book.